2015
DOI: 10.1007/s00234-015-1538-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution MRI using orbit surface coils for the evaluation of metastatic risk factors in 143 children with retinoblastoma

Abstract: The new imaging concept shows a trend towards improving the accuracy of detecting metastatic risk factors in children with retinoblastoma and is therefore recommended for pretherapeutic imaging and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
2
7
0
6
Order By: Relevance
“…However, an additional prospective study would be necessary to confirm this finding. In the interpretation of these results, it has to be considered that new image concepts using two orbit surface coils seem to improve the detection of choroidal invasion, especially of massive choroidal invasion further [29,31].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, an additional prospective study would be necessary to confirm this finding. In the interpretation of these results, it has to be considered that new image concepts using two orbit surface coils seem to improve the detection of choroidal invasion, especially of massive choroidal invasion further [29,31].…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, different scanners and surface coils (4-and 7-mm diameter) were used in their setting, which might have influenced the results. Newer image concepts using two orbit surface coils and newer MR scanners might further improve the detection rate for postlaminar optic nerve infiltration [29,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that PLONI can be diagnosed by the presence of optic nerve enhancement or tumor size (volume) . In a recent meta‐analysis, De Jong et al reported the sensitivity and specificity of MRI in detecting PLONI was 59% and 94%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that PLONI can be diagnosed by the presence of optic nerve enhancement or tumor size (volume). 19,20,[23][24][25]28,[30][31][32] In a recent meta-analysis, De Jong et al 18 reported the sensitivity and specificity of MRI in detecting PLONI was 59% and 94%, respectively. In our study, the optimal cutoff value was selected as the point when the Youden index was maximal and resulted in a higher sensitivity and accuracy for predicting PLONI (82% and 77%, respectively) compared to the aforementioned results.…”
Section: Discussionmentioning
confidence: 99%